2017
DOI: 10.1515/arsm-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Alvarado score: can it reduce unnecessary interventions for acute appendicitis in children?

Abstract: The purpose of the study is to compare the outcomes of surgical interventions for acute appendicitis with the values of the Alvarado score. We conducted the study on 572 patients that underwent surgical interventions for acute appendicitis. Retrospectively, based on the medical records, we calculated the MANTRELS score and compared the outcomes of the intervention with the values of the applied score. Almost one third of the patients with a MANTRELS score lower than 6 had negative appendectomies. These patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Chisalau et al [31] conducted a retrospective study in 572 children that underwent surgery for acute appendicitis using the Alvarado score. They found that 16.3% had a negative appendectomy, and that almost all patients with a high score confirmed the diagnosis after surgical intervention.…”
Section: Acute Appendicitis In Childrenmentioning
confidence: 99%
“…Chisalau et al [31] conducted a retrospective study in 572 children that underwent surgery for acute appendicitis using the Alvarado score. They found that 16.3% had a negative appendectomy, and that almost all patients with a high score confirmed the diagnosis after surgical intervention.…”
Section: Acute Appendicitis In Childrenmentioning
confidence: 99%